Effect of pmt gene overexpression on tropane alkaloid production in transformed root cultures of Datura metel and Hyoscyamus muticus - Moyano, Elisabet (Journal of experimental botany, 2003)
In order to increase the production of the pharmaceuticals hyoscyamine and scopolamine in hairy root cultures, a binary vector system was developed to introduce the T-DNA of the Ri plasmid together with the tobacco pmt gene under the control of CaMV 35S promoter, into the genome of Datura metel and Hyoscyamus muticus. This gene codes for putrescine:SAM N-methyltransferase (PMT; EC. 2.1.1.53), which catalyses the first committed step in the tropane alkaloid pathway. Hairy root cultures overexpressing the pmt gene aged faster and accumulated higher amounts of tropane alkaloids than control hairy roots. Both hyoscyamine and scopolamine production were improved in hairy root cultures of D. metel, whereas in H. muticus only hyoscyamine contents were increased by pmt gene overexpression. These roots have a high capacity to synthesize hyoscyamine, but their ability to convert it into scopolamine is very limited. The results indicate that the same biosynthetic pathway in two related plant species can be differently regulated, and overexpression of a given gene does not necessarily lead to a similar accumulation pattern of secondary metabolites